Organisation of goat research: The African perspective - Lebbie, S.H.B. (Institut de l'Elevage, 2000)
Goat research is organised at various levels in Africa with divers key players, interests and approaches. The paper presents an overview of these levels, the forces that mitigate against goat research and Development and suggests some measures that can address these constraints.